Fiscal space and public sector investments in infrastructure: A Brazilian case-study - José Roberto Afonso; Erika Amorim Araujo; Geraldo Biasoto Júnior (Institute for Applied Economic Research (ipea), 2015)
The Brazilian experience is of particular interest as a case study into the fiscal scope for public sector investments, especially in infrastructure. Brazil has one of the highest tax burdens in the world and, at the same time, the public sector has been registering a historic low in investment, even lower than the average levels seen elsewhere in Latin America. The idea of crating adequate fiscal space to allow for increased investment has been largely ignored at national level. The little that national debate has advanced so far on this issue has only produced at best a definition of the challenge. In this context, the paper does not intend to provide a ready-made solution for such large and varied challenges. Instead, it hopes to contribute in a small way to the development of debate, starting by raising and systemizing information and by pointing out possible alternatives, in a preliminary and perhaps somewhat provocative manner.
Keywords: H64; H62; H63; H30; 330